Self-shielded flux-cored welding wire capable of in-situ generating multi-component strengthening phase and preparation method thereof

By generating a self-protected flux-core welding wire with a multivariate reinforced phase in situ, the nitrogen and oxygen raw materials in the air and the oxygen-nitrogen reaction auxiliary agent are used to form VC+(Cr,Mn,Fe)7(C,B)3+(Cr,Mn,Mn ,Fe)3(C,B)+AlN+Al2O3 composite stacking alloy solves the problem of high cost and hardness of the existing wear-resistant alloy, and achieves high wear resistance and low cost effects.

CN116213994BActive Publication Date: 2025-02-07HEFEI UNIV OF TECH +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211630328.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-15
Publication Date
2025-02-07
Estimated Expiration
2042-12-15

AI Technical Summary

Technical Problem

The existing wear-resistant alloys have difficulties in the high cost and the combination of the hard phase and the bonding matrix phase, and the wear resistance and cracking tendency of the material are difficult to optimize simultaneously.

Method used

By generating self-protected flux-core welding wire with multi-strengthening phase in situ, using nitrogen and oxygen in the air as raw materials, combining oxygen-nitrogen reaction auxiliary agents, the concentration of N and O in the molten pool and the metallurgical reaction process are regulated, and VC+(Cr, Mn,Fe)7(C,B)3+(Cr,Mn,Fe)3(C,B)+AlN+Al2O3 composite stacking alloy.

Benefits of technology

In-situ generation of multiple types of boron carbide-nitride-oxide composite stacking materials is achieved, which improves the elastic modulus and wear resistance of the alloy, reduces costs, and avoids the generation of pores.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116213994B_ABST
    Figure CN116213994B_ABST
Patent Text Reader

Abstract

The invention discloses a self-shielded flux-cored welding wire and a preparation method for in-situ generation of multi-component strengthening phases, wherein the flux-cored welding wire comprises an outer skin and a flux core, and the flux core powder composition is as follows by mass percentage: 13-25% ferrovanadium, 2-6% aluminum-vanadium alloy, 12-22% ferroboron, 6-10% aluminum-silicon alloy powder, 2-4% carbon fiber powder, 2-3% graphite, 28-35% chromium powder, 6-9% manganese powder, 5-10% oxygen-nitrogen reaction auxiliary agent, and the balance is iron powder. The flux-cored welding wire provided by the invention is prepared by using N and O in the air as raw materials and melting the flux-cored welding wire in the air with an arc as a heat source, and in-situ self-generated hard phase VC+(Cr,Mn,Fe)7(C,B)3+(Cr,Mn,Fe)3(C,B)+AlN+Al2O3 in the deposited alloy. It has excellent wear resistance and low comprehensive cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal materials, and in particular relates to a self-shielded flux-cored welding wire capable of in-situ generating a multi-component strengthening phase and a preparation method thereof. Background Art

[0002] With the rapid development of science and technology, materials science and materials processing engineering have also achieved rapid development. People's requirements for material performance continue to reach new levels. In terms of the utilization of materials in the world, the consumption ratio is relatively large, the utilization rate is not high, the quality is poor, and the life is short. It cannot meet the requirements of the development of manufacturing and repair of atomic energy engineering equipment, transportation vehicles, metallurgical machinery, mining machinery, agricultural machinery, petrochemical machinery, etc. Among them, wear is one of the three main forms of material failure, and the economic losses caused each year are very huge.

[0003] Applying deposition technology to the field of mechanical equipment remanufacturing and repair can greatly improve the hardness and wear resistance of the workpiece and extend its service life. The wear resistance of the deposition alloy mainly depends on the type, form, quantity and distribution of the hard phase in the alloy structure. At present, the main types of hard phases are carbides, borides, nitrides and oxide ceramic phases. Carbides mainly include chromium carbides (Cr7C3, Cr 23 C6, Cr3C, etc.), is a common hard phase in iron-based cast iron materials. It is generally generated by the reaction of Cr and C in high-temperature metallurgical reactions. It is easy to obtain and has a high cost-effectiveness. In addition, there are MC-type carbides (M=Nb, Ti, W, V, etc.) with higher hardness and good thermal stability, which are extremely beneficial to enhancing the thermal stability and wear resistance of the alloy. However, WC is generally used as a particle doping, and there is a "sinking" problem. For VC, the tendency to combine with C to form VC in a strong carbide alloy system is weak, but once it is formed, it is not easy to deform and crack under wear conditions. The advantage of borides is that they have a high-hardness H-dimensional wear-resistant skeleton. For example, the hardness of M2B-type carbides can reach 2010HV, which is much higher than that of chromium carbides. High-boron alloys have higher-hardness borides as wear-resistant skeletons, and using the abundant B element in my country to replace expensive alloying elements such as Mo, Ni, and Cu can effectively reduce costs and improve the hardenability and hardenability of the alloy. However, simply adding B to form borides is relatively brittle. When B and C are added to the alloy at the same time, B can dissolve into carbides or replace C in carbides to form hard borides or composite boron-carbon compounds, while shifting the eutectic point to the left and increasing the amount of hard phases. Compared with carbides, nitrides have higher hardness and stability and are important hard phases for improving wear resistance. Oxide ceramic phases such as Al2O3 also have very high hardness, but are currently less used in wear-resistant alloys due to the difficulty in controlling the amount and morphology of their metallurgical generation, the tendency for a high oxygen content in the deposited alloy, and the tendency to float up and form slag in metallurgical reactions.

[0004] So far, the development trend of wear-resistant alloy technology in various countries is still to add some tungsten carbide to the deposited powder to obtain a hard phase in the alloy. The United States also uses the method of adding some chromium boride to the deposited powder, and Japan uses the method of directly adding vanadium carbide and niobium carbide to the deposited powder to obtain a hard phase and increase the red hardness of the alloy, that is, high temperature hardness and wear resistance. These methods have good effects, but the cost is high, and there is also a problem of combining the hard phase with the bonding matrix phase.

[0005] The use of metallurgical in-situ generation methods is conducive to solving the bonding defects caused by non-wetting and difficulty in wetting between the hard phase and the bonding phase matrix, while significantly reducing costs. In addition, the main components of air are nitrogen and oxygen, which provide an inexhaustible supply of natural and cheap raw materials for the in-situ generation of nitrides and oxides. If it is possible to regulate the chemical and physical metallurgical behavior in the air and in-situ self-generate multiple types of boron carbide-nitride-oxide deposited alloys, it will be possible to fully utilize the high hardness and high wear resistance of each hard phase while reducing the tendency of the material to crack, forming a multi-component composite strengthening effect, further expanding the system range of wear-resistant flux-cored welding wires, and adapting to the new requirements of the manufacture and repair of key wear-resistant equipment in modern manufacturing. Summary of the invention

[0006] Purpose of the invention: The technical problem to be solved by the present invention is to provide a self-shielded flux-cored welding wire with in-situ generation of multi-component strengthening phases and a preparation method thereof.

[0007] The technical problem that the present invention needs to solve is to provide a self-shielded flux-cored welding wire deposited alloy that generates multiple strengthening phases in situ.

[0008] Technical solution: To achieve the above-mentioned invention objectives, the present invention provides an in-situ self-generated multi-type boron carbide-nitride-oxide composite flux-cored welding wire, the flux-cored welding wire comprises an outer skin and a flux core, the flux core is a powder, and the flux core powder comprises the following components by mass percentage: 13-25% ferrovanadium, 2-6% aluminum-vanadium alloy, 12-22% ferroboron, 6-10% aluminum-silicon alloy powder, 2-4% carbon fiber powder, 2-3% graphite, 28-35% chromium powder, 6-9% manganese powder, 5-10% oxygen-nitrogen reaction auxiliary agent, and the balance is iron powder.

[0009] The oxygen-nitrogen reaction auxiliary agent comprises, by mass percentage, 6-10% chromium oxide, 25-40% lithium fluoride, 9-20% potassium fluoroaluminate, 18-30% rutile, 8-15% keratite, and 5-10% aluminum fluoride.

[0010] Preferably, the low carbon steel strip used in the flux-cored welding wire is H08A, and its composition is C: ≤0.1%, Mn: 0.3-0.55%, Si: ≤0.3%, S: ≤0.03%, P: ≤0.03%, and the balance is Fe.

[0011] Preferably, in terms of mass fraction, the vanadium content of the ferrovanadium is 30-40%, with the remainder being iron; the vanadium content of the aluminum-vanadium alloy is 35-42%, with the remainder being aluminum; the silicon content of the aluminum-silicon alloy powder is 11-13%, with the remainder being aluminum.

[0012] Preferably, the particle sizes of the ferrovanadium, aluminum-vanadium alloy, ferroboron, aluminum-silicon alloy powder, carbon fiber powder, graphite, chromium powder, manganese powder and iron powder components in the welding wire core are all greater than or equal to 150 mesh; the particle sizes of the chromium oxide, lithium fluoride, potassium fluoroaluminate, rutile, geholite and aluminum fluoride components in the oxygen-nitrogen reaction auxiliary agent are all greater than or equal to 200 mesh.

[0013] Preferably, the thickness×width of the low-carbon steel strip is 0.4×18 mm or 0.3×16 mm.

[0014] Preferably, the diameter of the flux-cored welding wire is 2.6-3.2 mm.

[0015] Preferably, the method for preparing the self-shielded flux-cored welding wire for in-situ generation of a multi-component strengthening phase comprises the following steps:

[0016] (1) The low carbon steel strip is rolled into a U shape by a forming roller, and then the flux core powder is added into the U-shaped groove by a powder feeding device at 54-58% of the total weight of the welding wire;

[0017] (2) The U-shaped groove is closed to wrap the core, and the wire is drawn and reduced in diameter step by step through a wire drawing die until the diameter reaches 2.8 to 3.2 mm to obtain the final product.

[0018] The present invention also includes a self-shielded flux-cored welding wire deposited alloy with in-situ generated multi-component strengthening phases, which is prepared in air by using the above-mentioned flux-cored welding wire through an arc melting method.

[0019] The in-situ self-generated hard phase in the wear-resistant alloy of the flux-cored welding wire deposited alloy specifically includes VC+(Cr, Mn, Fe)7(C, B)3+(Cr, Mn, Fe)3(C, B)+AlN+Al2O3.

[0020] The main functions of each component in the above-mentioned flux core are as follows: Ferrovanadium mainly provides V element, which is dissolved in the matrix to improve the strength of the matrix and reacts with C to form VC. Aluminum-vanadium alloy not only provides Al, reacts with air to form Al2O3 and AlN, but also serves as an important supplement to ferrovanadium, providing V to facilitate the formation of VC. Aluminum-silicon alloy provides Al, reacts with air to form Al2O3 and AlN, and uses silicon as a strengthening matrix phase, and has a deoxidizing effect, regulating the O content in the deposited metal entering the air. Adding Al in the form of an alloy is beneficial to increase the thermal stability of Al, avoid excessive burning in the early stage, and provide a component basis for the formation of Al2O3 and AlN. Ferroboron, carbon fiber powder and graphite are added together to facilitate the reaction with the alloy to form boron carbide. This avoids the brittleness of the material caused by the single addition of boron or carbon, and greatly optimizes the alloy structure and wear resistance. The purpose of adding chromium powder and manganese powder is to generate chromium-rich boron carbides such as (Cr, Mn, Fe)7(C, B)3 and (Cr, Mn, Fe)3(C, B) in situ, and manganese powder also has the function of deoxidation and generating manganese air pockets to moderately reduce the air partial pressure. Compared with Cr, V is a weak carbide-forming element. Therefore, if the addition of chromium powder exceeds 35%, VC cannot be formed and wear resistance is reduced.

[0021] The chromium oxide in the oxygen-nitrogen reaction auxiliary agent can undergo a substitution reaction with aluminum to form Al2O3. The functions of lithium fluoride, potassium fluoroaluminate, and fluorine fluoride are: to provide fluoride ions to reduce the H content caused by the entry of moisture in the air into the molten pool; to provide aluminum, which is conducive to the formation of aluminum nitrides and oxides; the presence of Li and K can improve the arc stability. Rutile and geologic stone are used to form thin slag and improve the process performance during arc melting. The addition amount of oxygen-nitrogen reaction auxiliary agent ranges from 5 to 10%. If it is less than 5%, the deposited alloy will form pores; if it is higher than 10%, the deposited alloy will have poor forming, slag removal will be difficult, and the wear resistance will be significantly reduced.

[0022] It can be understood from the above technical scheme and the brief description of the functions of each component in the core that the present invention provides an in-situ self-generated multi-type boron carbide-nitride-oxide composite stacking material, which realizes the metallurgical process of arc melting and solidification in the air, and uses N and O in the air as raw materials to induce part of N and O to penetrate into the metal melt, react with Al added thereto, and form Al2O3 and AlN at the same time, while other elements form multi-type chromium-rich boron carbides in the metallurgical process. The key to the technical implementation is to use the oxygen-nitrogen reaction auxiliary agent added to the core to control the concentration of N and O in the molten pool and the metallurgical reaction process, so that pores will not be generated in the end, and a new type of VC+(Cr, Mn, Fe)7(C, B)3+(Cr, Mn, Fe)3(C, B)+AlN+Al2O3 composite stacking alloy is formed in an in-situ generated manner. In particular, O, as an active element, can react chemically with a variety of elements, and its control is very difficult.

[0023] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0024] (1) Breaking through the traditional method of strengthening the metal matrix with a single or two types of carbides, borides, nitrides or oxides, a multi-type boron carbide-nitride-oxide composite deposit material is generated in situ, which greatly increases the elastic modulus and wear resistance of the deposited alloy.

[0025] (2) Using air, whose main components are O and N, as a basic raw material for the preparation of wear-resistant materials greatly expands the source of raw materials for wear-resistant materials and forms the principles and technical approaches of high-temperature physical, chemical and metallurgical metallurgy in air.

[0026] (3) No N pores and CO pores are generated, and the deposited alloy has beautiful shape.

[0027] (4) Low overall cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a typical microstructure of the stacking layer of the stacking alloy of Example 1;

[0029] Figure 2 The microstructure and EDS composition analysis results of the VC hard phase of the stacked alloy of Example 1;

[0030] Figure 3 It is the microstructure and EDS composition analysis results of the deposited alloy chromium-rich boron carbide (Cr, Mn, Fe)7(C, B)3+(Cr, Mn, Fe)3(C, B), nitride and oxide AlN+Al2O3 of Example 1. DETAILED DESCRIPTION

[0031] The present invention can be better understood according to the following examples. However, the specific core component ratios, process conditions and results described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims. Among them, the vanadium content of the ferrovanadium used in the following examples is 30-40%, and the rest is iron; the vanadium content of the ferrovanadium is 30-40%, and the rest is iron; the vanadium content of the vanadium aluminum alloy is 35-42%, and the rest is aluminum; the silicon content of the aluminum silicon alloy is 11-13%, and the rest is aluminum.

[0032] Example 1 Preparation of self-shielded flux-cored welding wire and flux-cored welding wire deposited alloy with in-situ generation of multi-component strengthening phase

[0033] A self-shielded flux-cored welding wire for in-situ generation of multi-component strengthening phases comprises a low-carbon steel strip and flux-cored powder, wherein the flux-cored powder is filled in the steel strip. The composition of the steel strip H08A is C: 0.1%, Mn: 0.3-0.55%, Si: 0.3%, S: ≤0.03%, P: ≤0.03%. The flux-cored components are prepared according to the following mass: 130g of ferrovanadium, 60g of aluminum-vanadium alloy, 120g of ferroboron, 80g of aluminum-silicon alloy powder, 20g of carbon fiber powder, 20g of graphite, 350g of chromium powder, 60g of manganese powder, 100g of oxygen-nitrogen reaction auxiliary agent, and 60g of iron powder. The composition of the oxygen-nitrogen reaction auxiliary agent is as follows by mass percentage: 6% of chromium oxide, 25% of lithium fluoride, 20% of potassium fluoroaluminate, 25% of rutile, 15% of keratite, and 9% of aluminum fluoride. Ferrovanadium, aluminum-vanadium alloy, ferroboron, aluminum-silicon alloy powder, carbon fiber powder, graphite, chromium powder, manganese powder and iron powder are sieved through a 150-mesh sieve; chromium oxide, lithium fluoride, potassium fluoroaluminate, rutile, geholite and aluminum fluoride components in the oxygen-nitrogen reaction auxiliary agent are sieved through a 200-mesh sieve. The various powders are placed in a powder mixer and mixed for 60 minutes, and then the mixed powder is added to a U-shaped 0.3×16mm H08A carbon steel belt groove with a filling rate of 54%. The U-shaped groove is then closed to wrap the powder. Then it is passed through wire drawing dies with diameters of 4.2mm, 3.8mm, 3.5mm and 3.2mm, and drawn and reduced one by one, and finally a composite flux-cored welding wire product with a diameter of 3.2mm is obtained.

[0034] Preparation of flux-cored wire deposited alloy: The flux-cored wire product was deposited using an arc welding machine. The arc heating current was 300-340A, the voltage was 30-35V, the arc moving speed was 0.3m / min, the interlayer temperature was controlled at 150-200℃, and 5 layers were deposited. The formability, hard phase composition, hardness, and mass wear rate of the deposited layer alloy are shown in Table 1. Figure 1 This is a typical organizational morphology of the deposited layer, in which various types and forms of composite hard phases can be seen. Figure 2 This is the EDS analysis result of the granular precipitate, proving that it is VC. Figure 3 This is a typical area magnified SEM image and its surface scanning energy spectrum element distribution. The results show that the lath-shaped, small block-shaped and stripe-shaped precipitates are chromium-rich boron carbides (Cr, Mn, Fe)7(C, B)3+(Cr, Mn, Fe)3(C, B), and the black small-sized polygonal or granular precipitates are nitrides and oxides AlN+Al2O3.

[0035] Example 2 Preparation of self-shielded flux-cored welding wire and flux-cored welding wire deposited alloy with in-situ generation of multi-component strengthening phase

[0036] A self-shielded flux-cored welding wire for in-situ generation of multi-component strengthening phases comprises a low-carbon steel strip and a flux core, wherein the flux core is filled in the steel strip. The composition of the steel strip H08A is C: 0.1%, Mn: 0.3-0.55%, Si: 0.3%, S: ≤0.03%, P: ≤0.03%. The flux core composition is prepared according to the following mass: 250g of ferrovanadium, 30g of aluminum-vanadium alloy, 150g of ferroboron, 60g of aluminum-silicon alloy powder, 40g of carbon fiber powder, 20g of graphite, 300g of chromium powder, 90g of manganese powder, 60g of oxygen-nitrogen reaction auxiliary agent, and 0g of iron powder. The above oxygen-nitrogen reaction auxiliary agent is composed of 10% chromium oxide, 30% lithium fluoride, 10% potassium fluoroaluminate, 30% rutile, 10% keratite, and 10% aluminum fluoride in mass percentage. Ferrovanadium, aluminum-vanadium alloy, ferroboron, aluminum-silicon alloy powder, carbon fiber powder, graphite, chromium powder and manganese powder are sieved through a 150-mesh sieve; chromium oxide, lithium fluoride, potassium fluoroaluminate, rutile, geholite and aluminum fluoride components in the oxygen-nitrogen reaction auxiliary agent are sieved through a 200-mesh sieve. The various powders are placed in a powder mixer and mixed for 60 minutes, and then the mixed powder is added to a U-shaped 0.4×18mm H08A carbon steel belt groove with a filling rate of 56%. The U-shaped groove is then closed to wrap the powder. Then it is passed through wire drawing dies with diameters of 4.2mm, 3.8mm, 3.5mm, 3.2mm and 2.8mm, and is drawn and reduced one by one to finally obtain a flux-cored welding wire product with a diameter of 2.8mm.

[0037] Preparation of flux-cored wire deposited alloy: The composite flux-cored wire product was deposited using an arc welding machine. The arc heating current was 300-340A, the voltage was 30-35V, the arc moving speed was 0.3m / min, the interlayer temperature was controlled at 150-200℃, and 5 layers were deposited. The formability, hard phase composition, hardness, and mass wear rate of the deposited layer alloy are shown in Table 1.

[0038] Example 3 Preparation of self-shielded flux-cored welding wire and flux-cored welding wire deposited alloy with in-situ generation of multi-component strengthening phase

[0039] An in-situ self-generated multi-type boron carbide-nitride-oxide composite flux-cored welding wire comprises a low-carbon steel strip and a flux core, wherein the flux core is filled in the steel strip. The composition of the steel strip H08A is C: 0.1%, Mn: 0.3-0.55%, Si: 0.3%, S: ≤0.03%, P: ≤0.03%. The flux core composition is prepared according to the following mass: 150g of ferrovanadium, 20g of aluminum-vanadium alloy, 220g of ferroboron, 100g of aluminum-silicon alloy powder, 40g of carbon fiber powder, 30g of graphite, 280g of chromium powder, 70g of manganese powder, 50g of oxygen-nitrogen reaction auxiliary agent, and 40g of iron powder. The above oxygen-nitrogen reaction auxiliary agent is composed of 8% chromium oxide, 40% lithium fluoride, 9% potassium fluoroaluminate, 28% rutile, 10% keratite, and 5% aluminum fluoride in mass percentage. Ferrovanadium, aluminum-vanadium alloy, ferroboron, aluminum-silicon alloy powder, carbon fiber powder, graphite, chromium powder, manganese powder and iron powder are sieved through a 150-mesh sieve; chromium oxide, lithium fluoride, potassium fluoroaluminate, rutile, geholite and aluminum fluoride components in the oxygen-nitrogen reaction auxiliary agent are sieved through a 200-mesh sieve. The various powders are placed in a powder mixer and mixed for 60 minutes, and then the mixed powder is added to a U-shaped 0.3×16mm H08A carbon steel belt groove with a filling rate of 58%. The U-shaped groove is then closed to wrap the powder. Then it is passed through wire drawing dies with diameters of 4.2mm, 3.8mm, 3.5mm, 3.2mm, 2.8mm and 2.6mm, and drawn and reduced one by one, and finally a flux-cored welding wire product with a diameter of 2.6mm is obtained.

[0040] Preparation of flux-cored wire deposited alloy: The flux-cored wire product was deposited using an arc welding machine. The arc heating current was 300-340A, the voltage was 30-35V, the arc moving speed was 0.3m / min, the interlayer temperature was controlled at 150-200℃, and 5 layers were deposited. The formability, hard phase composition, hardness, and mass wear rate of the deposited layer alloy are shown in Table 1.

[0041] Example 4 Preparation of self-shielded flux-cored welding wire and flux-cored welding wire deposited alloy with in-situ generation of multi-component strengthening phase

[0042] A self-shielded flux-cored welding wire for in-situ generation of multi-component strengthening phases comprises a low-carbon steel strip and a flux core, wherein the flux core is filled in the steel strip. The composition of the steel strip H08A is C: 0.1%, Mn: 0.3-0.55%, Si: 0.3%, S: ≤0.03%, P: ≤0.03%. The flux core composition is prepared according to the following mass: 150g of ferrovanadium, 40g of aluminum-vanadium alloy, 200g of ferroboron, 60g of aluminum-silicon alloy powder, 30g of carbon fiber powder, 20g of graphite, 320g of chromium powder, 80g of manganese powder, 90g of oxygen-nitrogen reaction auxiliary agent, and 10g of iron powder. The above oxygen-nitrogen reaction auxiliary agent is composed of 8% chromium oxide, 40% lithium fluoride, 16% potassium fluoroaluminate, 18% rutile, 8% keratite, and 10% aluminum fluoride in terms of mass percentage. Ferrovanadium, aluminum-vanadium alloy, ferroboron, aluminum-silicon alloy powder, carbon fiber powder, graphite, chromium powder, manganese powder and iron powder are sieved through a 150-mesh sieve; chromium oxide, lithium fluoride, potassium fluoroaluminate, rutile, geholite and aluminum fluoride components in the oxygen-nitrogen reaction auxiliary agent are sieved through a 200-mesh sieve. The various powders are placed in a powder mixer and mixed for 60 minutes, and then the mixed powder is added to a U-shaped 0.4×18mm H08A carbon steel belt groove with a filling rate of 56%. The U-shaped groove is then closed to wrap the powder. Then it is passed through wire drawing dies with diameters of 4.2mm, 3.8mm, 3.5mm, 3.2mm and 2.8mm, and is drawn and reduced one by one to finally obtain a flux-cored welding wire product with a diameter of 2.8mm.

[0043] Preparation of flux-cored wire deposited alloy: deposited by arc welding machine. The arc heating current is 300-340A, the voltage is 30-35V, the arc moving speed is 0.3m / min, the interlayer temperature is controlled at 150-200℃, and 5 layers are deposited. The formability, hard phase composition, hardness and mass wear rate of the deposited layer alloy are shown in Table 1.

[0044] Comparative Example 1 Preparation of Self-shielded Flux-cored Welding Wire and Flux-cored Welding Wire Deposition Alloy with In-situ Generation of Multi-component Strengthening Phase

[0045] A self-shielded flux-cored welding wire for in-situ generation of multi-component strengthening phases comprises a low-carbon steel strip and a flux core, wherein the flux core is filled in the steel strip. The composition of the steel strip H08A is C: 0.1%, Mn: 0.3-0.55%, Si: 0.3%, S: ≤0.03%, P: ≤0.03%. The flux core composition is prepared according to the following mass: 130g of ferrovanadium, 40g of aluminum-vanadium alloy, 180g of ferroboron, 60g of aluminum-silicon alloy powder, 30g of carbon fiber powder, 25g of graphite, 400g of chromium powder, 60g of manganese powder, 50g of oxygen-nitrogen reaction auxiliary agent, and 25g of iron powder. The above oxygen-nitrogen reaction auxiliary agent is composed of 9% chromium oxide, 35% lithium fluoride, 10% potassium fluoroaluminate, 25% rutile, 12% keratite, and 9% aluminum fluoride in mass percentage. Ferrovanadium, aluminum-vanadium alloy, ferroboron, aluminum-silicon alloy powder, carbon fiber powder, graphite, chromium powder, manganese powder and iron powder are sieved through a 150-mesh sieve; chromium oxide, lithium fluoride, potassium fluoroaluminate, rutile, geholite and aluminum fluoride components in the oxygen-nitrogen reaction auxiliary agent are sieved through a 200-mesh sieve. The various powders are placed in a powder mixer and mixed for 60 minutes, and then the mixed powder is added to a U-shaped 0.3×16mm H08A carbon steel belt groove with a filling rate of 57%. The U-shaped groove is then closed to wrap the powder. Then it is passed through wire drawing dies with diameters of 4.2mm, 3.8mm, 3.5mm, 3.2mm and 2.8mm, and drawn and reduced one by one, and finally a flux-cored welding wire product with a diameter of 2.8mm is obtained.

[0046] Preparation of flux-cored wire deposited alloy: The flux-cored wire product was deposited using an arc welding machine. The arc heating current was 300-340A, the voltage was 30-35V, the arc moving speed was 0.3m / min, the interlayer temperature was controlled at 150-200℃, and 5 layers were deposited. The formability, hard phase composition, hardness, and mass wear rate of the deposited layer alloy are shown in Table 1.

[0047] Comparative Example 2 Preparation of Self-shielded Flux-cored Welding Wire and Flux-cored Welding Wire Deposition Alloy with In-situ Generation of Multi-element Strengthening Phase

[0048] A self-shielded flux-cored welding wire for in-situ generation of multi-component strengthening phases comprises a low-carbon steel strip and a flux core, wherein the flux core is filled in the steel strip. The composition of the steel strip H08A is C: 0.1%, Mn: 0.3-0.55%, Si: 0.3%, S: ≤0.03%, P: ≤0.03%. The flux core composition is prepared according to the following mass: 250g of ferrovanadium, 40g of aluminum-vanadium alloy, 150g of ferroboron, 100g of aluminum-silicon alloy powder, 20g of carbon fiber powder, 30g of graphite, 300g of chromium powder, 70g of manganese powder, 20g of oxygen-nitrogen reaction auxiliary agent, and 20g of iron powder. The above oxygen-nitrogen reaction auxiliary agent is composed of 9% chromium oxide, 30% lithium fluoride, 20% potassium fluoroaluminate, 18% rutile, 13% keratite, and 10% aluminum fluoride in terms of mass percentage. Ferrovanadium, aluminum-vanadium alloy, ferroboron, aluminum-silicon alloy powder, carbon fiber powder, graphite, chromium powder, manganese powder and iron powder are sieved through a 150-mesh sieve; chromium oxide, lithium fluoride, potassium fluoroaluminate, rutile, geholite and aluminum fluoride components in the oxygen-nitrogen reaction auxiliary agent are sieved through a 200-mesh sieve. The various powders are placed in a powder mixer and mixed for 60 minutes, and then the mixed powder is added to a U-shaped 0.3×16mm H08A carbon steel belt groove with a filling rate of 58%. The U-shaped groove is then closed to wrap the powder. Then it is passed through wire drawing dies with diameters of 4.2mm, 3.8mm, 3.5mm, 3.2mm, 2.8mm and 2.6mm, and drawn and reduced one by one, and finally a flux-cored welding wire product with a diameter of 2.6mm is obtained.

[0049] Preparation of flux-cored wire deposited alloy: The flux-cored wire product was deposited using an arc welding machine. The arc heating current was 300-340A, the voltage was 30-35V, the arc moving speed was 0.3m / min, the interlayer temperature was controlled at 150-200℃, and 5 layers were deposited. The formability, hard phase composition, hardness, and mass wear rate of the deposited layer alloy are shown in Table 1.

[0050] Comparative Example 3 Preparation of Self-shielded Flux-cored Welding Wire and Flux-cored Welding Wire Deposition Alloy with In-situ Generation of Multi-element Strengthening Phase

[0051] A self-shielded flux-cored welding wire for in-situ generation of multi-component strengthening phases comprises a low-carbon steel strip and a flux core, wherein the flux core is filled in the steel strip. The composition of the steel strip H08A is C: 0.1%, Mn: 0.3-0.55%, Si: 0.3%, S: ≤0.03%, P: ≤0.03%. The flux core composition is prepared according to the following mass: 150g of ferrovanadium, 50g of aluminum-vanadium alloy, 160g of ferroboron, 80g of aluminum-silicon alloy powder, 40g of carbon fiber powder, 20g of graphite, 280g of chromium powder, 90g of manganese powder, 130g of oxygen-nitrogen reaction auxiliary agent, and 0g of iron powder. The above oxygen-nitrogen reaction auxiliary agent is composed of 6% of chromium oxide, 38% of lithium fluoride, 15% of potassium fluoroaluminate, 25% of rutile, 8% of keratite, and 8% of aluminum fluoride in terms of mass percentage. Ferrovanadium, aluminum-vanadium alloy, ferroboron, aluminum-silicon alloy powder, carbon fiber powder, graphite, chromium powder, manganese powder and iron powder are sieved through a 150-mesh sieve; chromium oxide, lithium fluoride, potassium fluoroaluminate, rutile, geholite and aluminum fluoride components in the oxygen-nitrogen reaction auxiliary agent are sieved through a 200-mesh sieve. The various powders are placed in a powder mixer and mixed for 60 minutes, and then the mixed powder is added to a U-shaped 0.3×16mm H08A carbon steel belt groove with a filling rate of 56%. The U-shaped groove is then closed to wrap the powder. Then it is passed through wire drawing dies with diameters of 4.2mm, 3.8mm, 3.5mm and 3.2mm, and drawn and reduced one by one, and finally a flux-cored welding wire product with a diameter of 3.2mm is obtained.

[0052] Preparation of flux-cored wire deposited alloy: The flux-cored wire product is deposited using an arc welding machine. The arc heating current is 300-340A, the voltage is 30-35V, the arc moving speed is 0.3m / min, and the interlayer temperature is controlled at 150-200℃. The formability, hard phase composition, hardness, and mass wear rate of the deposited layer alloy are shown in Table 1.

[0053] Porosity sensitivity test in Table 1: Flat plate welding was performed on a test plate of 200mm×80mm×20mm. After cooling for 3 to 5 minutes, the slag was knocked off with a hammer. The number of pores on the weld surface was observed and recorded as surface pores. The weld was polished layer by layer using a grinder, and the number of subcutaneous pores in the weld was observed and recorded as internal pores. The porosity sensitivity of the weld metal of different samples was evaluated based on the number of pores recorded during the test.

[0054] The evaluation of slag removal performance refers to the provisions of the slag removal performance in the 1989 National Welding Rod Evaluation Competition. The same test plate as the coverage test is used. The slag removal rate is calculated as follows:

[0055]

[0056] Where, D——slag removal rate (%);

[0057] L——total length of weld (mm);

[0058] L0——Unslag-free length (mm);

[0059] L1——severe sticky residue length (mm);

[0060] L2——Length of slight sticky residue (mm).

[0061] A slag removal rate exceeding 90% indicates excellent slag removal performance.

[0062] Analysis of the hard phase composition of the alloy structure: The test was carried out using a scanning electron microscope (SEM) and an energy dispersive X-ray spectrometer (EDS).

[0063] The hardness of the deposited alloy was measured using a HR-150A Rockwell hardness tester. Five hardness points were taken for each test sample and the average hardness value was calculated.

[0064] The wear resistance test was conducted using a HT-1000 friction and wear tester with a pressure load of 15N, a rotation speed of 350r / min, a friction radius of 3.5mm, and a wear time of 30min. The grinding material was a silicon nitride (Si3N4) ceramic ball with a diameter of 5mm. The mass of the sample before and after the test was weighed with a precision balance with an accuracy of 0.1mg, and the wear rate was calculated using the following formula:

[0065]

[0066] Where, W is the mass wear rate (g / m);

[0067] m1——weight of the sample before the test (g);

[0068] m2——weight of the sample after the test (g);

[0069] L——Total distance of friction sliding (m).

[0070] The smaller the mass wear rate, the better the wear resistance.

[0071] Table 1 Formability of the alloys of the deposited layer of each embodiment, hardness, and mass wear rate

[0072]

Claims

1. A self-shielded flux-cored welding wire with in-situ generation of multi-component strengthening phase, characterized in that: The flux-cored welding wire comprises an outer sheath and a flux core, wherein the flux core is a powder, and the flux core powder comprises the following components by mass percentage: 13-25% ferrovanadium, 2-6% aluminum-vanadium alloy, 12-22% ferroboron, 6-10% aluminum-silicon alloy powder, 2-4% carbon fiber powder, 2-3% graphite, 28-35% chromium powder, 6-9% manganese powder, 5-10% oxygen-nitrogen reaction auxiliary agent, and the balance is iron powder, and the oxygen-nitrogen reaction auxiliary agent comprises by mass percentage: 6-10% chromium oxide, 25-40% lithium fluoride, 9-20% potassium fluoroaluminate, 18-30% rutile, 8-15% keratite, and 5-10% aluminum fluoride.

2. The self-shielded flux-cored welding wire with in-situ generation of multiple strengthening phases according to claim 1, characterized in that: The outer skin is a low-carbon steel strip H08A, and its composition is C: ≤0.1%, Mn: 0.3-0.55%, Si: ≤0.3%, S: ≤0.03%, P: ≤0.03%, and the balance is Fe.

3. The self-shielded flux-cored welding wire with in-situ generation of multiple strengthening phases according to claim 1, characterized in that: In terms of mass fraction, the vanadium content of the ferrovanadium is 30-40%, and the rest is iron; the vanadium content of the aluminum-vanadium alloy is 35-42%, and the rest is aluminum; the silicon content of the aluminum-silicon alloy powder is 11-13%, and the rest is aluminum.

4. The self-shielded flux-cored welding wire with in-situ generation of multiple strengthening phases according to claim 1, characterized in that: The particle sizes of the ferrovanadium, aluminum-vanadium alloy, ferroboron, aluminum-silicon alloy powder, carbon fiber powder, graphite, chromium powder, manganese powder and iron powder components in the core are all greater than or equal to 150 meshes; the particle sizes of the chromium oxide, lithium fluoride, potassium fluoroaluminate, rutile, gesso and aluminum fluoride components in the oxygen-nitrogen reaction auxiliary agent are all greater than or equal to 200 meshes.

5. The self-shielded flux-cored welding wire with in-situ generation of multiple strengthening phases according to claim 2, characterized in that: The thickness×width of the low carbon steel strip H08A is 0.4×18 mm or 0.3×16 mm.

6. The self-shielded flux-cored welding wire with in-situ generation of multiple strengthening phases according to claim 1, characterized in that: The diameter of the flux-cored welding wire is 2.6-3.2 mm.

7. The method for preparing the self-shielded flux-cored welding wire with in-situ generation of multiple strengthening phases according to claim 1, characterized in that: The steps include: (1) Use a forming roller to roll the low carbon steel strip into a U shape, and then add the flux core powder into the U-shaped groove at a rate of 54-58% of the total weight of the welding wire through a powder feeding device; (2) The U-shaped groove is closed to wrap the core, and the wire is drawn and reduced in diameter step by step through a wire drawing die until its diameter reaches 2.6 to 3.2 mm to obtain the final product.

8. A self-shielded flux-cored welding wire deposited alloy with in-situ generation of multi-component strengthening phases, characterized in that: The self-shielded flux-cored welding wire deposited alloy with in-situ generated multi-component strengthening phase is prepared in air by an arc melting method using the flux-cored welding wire described in any one of claims 1 to 6.

9. The self-shielded flux-cored welding wire deposited alloy with in-situ generation of multi-component strengthening phase according to claim 8, characterized in that: The in-situ self-generated hard phase in the wear-resistant alloy of the self-shielded flux-cored welding wire deposited alloy specifically includes VC+(Cr,Mn,Fe)7(C,B)3+(Cr,Mn,Fe)3(C,B)+AlN+Al2O3.

Citation Information

Patent Citations

  • Flux-cored steel belt for build-up welding and preparation method thereof

    CN101306493A